Association between vitamin D receptor gene polymorphisms and athletic performance in Chinese male youth soccer players - Shidong Yang; Wei Zhang; Meng Jia; Haichun Chen (PeerJ)
Background The relationship between the vitamin D receptor (VDR) gene and muscle strength has been extensively investigated; however, the findings of this research remain inconclusive. The aim of this study was to evaluate the association between VDR variants (ApaI rs797523, BsmI rs1544410, and FokI rs2228570 genotypes) and athletic performance in youth soccer players in China. Materials and Methods A total of 142 male soccer players (73 from an elite group and 69 from a sub-lite group) aged 13–15 years, and 107 controls (13- to 14-year-old students) were recruited for this study. We measured height, weight, speed, explosive power, anaerobic endurance, and aerobic endurance in both the elite and sub-elite athletes. ApaI, BsmI and FokI genotypes were detected in controls, elite, and sub-elite soccer players with the single-nucleotide polymorphism (SNP) technique. The χ2 test was applied to analyze the correlation between genotype distribution and allelic frequency in elite and sub-elite athletes and controls. One-way analysis of variance and Bonferroni’s post hoc test were implemented to analyze the differences in parameters among groups, and statistical significance was set at p ≤ 0.05. Results (1) The genotype distributions of the ApaI, BsmI, and FokI in controls, elite, and sub-elite soccer players were consistent with the Hardy–Weinberg equilibrium (HWE) results, except for the BsmI genotype distribution in control s (χ2 = 7.396, df = 1, p = 0.025). (2) The BsmI AG frequency in the controls and sub-elite players was significantly higher than in the elite players (χ2 = 6.4, df = 1, p = 0.011; χ2 = 4.50, df = 1, p = 0.034, respectively). The frequency of the FokI TT genotype in the controls was significantly higher than in the elite and sub-elite players (χ2 = 12.737, df = 1, p < 0.001, χ2 = 8.805, df = 1, p = 0.003, respectively). The frequency of the ApaI A in the elite players was significantly lower than that in the controls and sub-elite players (χ2 = 3.765, df = 1, p = 0.05; χ2 = 12.19, df = 1, p < 0.001 respectively). (3) ApaI CC players had longer distances in the standing long jump (SLJ) (p = 0.026) and shorter times in the 30-m run (p = 0.003) than ApaI AC players. Additionally, ApaI AA players had significantly longer Yo-Yo Intermittent Recovery Test Level 1 (YYIR1) running distances compared to ApaI AC players (p = 0.002). Conclusion Chinese elite youth soccer players are more likely to possess the ApaI CC genotype and are less likely than sub-elite players to have the BsmI A alleles. Additionally, the ApaI CC genotype is associated with better speed and explosive power among Chinese elite youth soccer players.